Adaptation of Davies, Gilbert and Gaia\'s theory with the concepts of Quranic verses - AliAkbar Imani; Fatemeh Saki (تحقیقات کاربردی علوم جغرافیایی)
The concept of balance has been applied  into various areas such as  Davis's evolutionary perspective,  the field of systemic epistemology as well as  the concepts and interpretations of the Quranic verses about the phenomena of the earth's surface.  Davis's theory about the balance of forms and morphology states that the forms of the earth in longer periods of time are evolving or gradually decaying, in other words, they have progressive and irreversible change. This concept has strong entropy maximization and positive feedback, but without a doubt, what is meant by the concept of balance in Davis's point of view is comparable to what is meant by the systemic point of view and the concepts of verses from the Quran that show evolution, order, continuity and balance in phenomena. In this regard, there are three points of view that can be examined. They are similar considering two of the points of view, however, there are differences  regarding the time frame required for the destruction of the mountains.However, according to Gilbert's point of view, the appearance of the form and process can be associated to mechanisms of negative feedback. The results are subject to change and fluctuation with different intensities and cause the surface forms of the earth to change their shape according to the intensity of the fluctuation which does not contradict with the Quranic verses. Additionally,  Gaia's perspective, which examines life and its effects on the earth according to the positive and negative feedbacks in a system, is consistent with the concepts of the Quranic verses. This study is a fundamental research that aims to compare the three theories of Davis, Gilbert and Gaya with the verses of the Quran to discover their similarities and differences.